5
$\begingroup$

I was trying to do this integral $$\int \sqrt{1+x^2}dx$$ I saw this question and its' use of hyperbolic functions. I did it with binomial differential method since the given integral is in a form of $\int x^m(a+bx^n)^p\,dx$ and I spent a lot of time on it so I would like to see if it can be done this way and where did I go wrong. $$\int(1+x^2)^\frac{1}{2}dx$$ $m=0$, $n=2$, $p=\frac{1}{2}$

Because $\frac{m+1}{n}+p \in \mathbb Z$ I used substitution $x^{-2}+1=t^2$.
From there I got:
$$-\frac{dx}{x^3}=t\,dt$$ $$x=\frac{1}{\sqrt {t^2-1}}$$ $$t=\frac{\sqrt{1+x^2}}{x}$$

I expanded the original with $x^4$:
$$\int \frac{x^4\sqrt{1+x^2}dx}{x^4}=\int \left(\frac{1}{\sqrt{t^2-1}}\right)^4t(-tdt)=\int\frac{-t^2dt}{(t^2-1)^2}$$

Now I used partial integration:
$u=t$,
$du=dt$,
$dv=\frac{-tdt}{(t^2-1)^2}$,
$v=\frac{1}{2(t^2-1)}$

Then
$$\begin{align} \int\frac{-t^2dt}{(t^2-1)^2} &=\frac{t}{2(t^2-1)}-\frac{1}{2}\int \frac{dt}{t^2-1}= \\ &=\frac{t}{2(t^2-1)}-\frac{1}{2}\frac{1}{2}\ln\frac{t-1}{t+1}= \\ &=\frac{\frac{\sqrt{1+x^2}}{x}}{2\left(\left(\frac{\sqrt{1+x^2}}{x}\right)^2-1\right)}-\frac{1}{4}\ln\frac{\frac{\sqrt{1+x^2}}{x}-1}{\frac{\sqrt{1+x^2}}{x}+1}= \\ &=\frac{x\sqrt{1+x^2}}{2}-\frac{1}{4}\ln\frac{\sqrt{1+x^2}-x}{\sqrt{1+x^2}+x}=\\ &=\frac{x\sqrt{1+x^2}}{2}-\frac{1}{4}\ln\frac{\sqrt{1+x^2}-x}{\sqrt{1+x^2}+x}\cdot\frac{\sqrt{1+x^2}-x}{\sqrt{1+x^2}-x}=\\ &=\frac{x\sqrt{1+x^2}}{2}-\frac{1}{4}\ln(\sqrt{1+x^2}-x)^2=\\ &=\frac{x\sqrt{1+x^2}}{2}-\frac{1}{2}\ln(\sqrt{1+x^2}-x)+C \end{align}$$

The solution is
$$\frac{x\sqrt{1+x^2}}{2}+\frac{1}{2}\ln(x+\sqrt{1+x^2})+C$$ My solution looks very similar, so where did I go wrong?

$\endgroup$
1
  • $\begingroup$ You can also calculate your integral by using the substitution x = tanu $\endgroup$
    – al.al.
    Feb 21 '18 at 12:06
9
$\begingroup$

Solutions are same. Observe that $\sqrt{1+x^2}-x=\frac{1+x^2-x^2}{\sqrt{1+x^2}+x}=\frac{1}{\sqrt{1+x^2}+x}$.

$\endgroup$
1
  • $\begingroup$ Nice, I did it for so long I didn't even realize it was the same :D $\endgroup$
    – Plexus
    Feb 21 '18 at 12:09
7
$\begingroup$

Let $ x = \sinh \theta$, then set $$I=\int \sqrt{1+x^2}dx$$ Whence \begin{align} I &= \int \sqrt{1+x^2}dx \\ &= \int \sqrt{1+\sinh^2 \theta}\cosh \theta d \theta \\ &= \int \cosh^2 \theta d \theta \\ &= \frac{1}{2}\int 1 + \cosh 2 \theta d \theta \\ &= \frac{1}{2}\theta+\frac{1}{4}\sinh 2 \theta + c\\ &= \frac{1}{2}\sinh^{-1}x+\frac{1}{2}x\sqrt{1+x^2}+c\\ &=\frac{1}{2}\ln(x + \sqrt{1+x^2})+\frac{1}{2}x\sqrt{1+x^2}+c \end{align}

$\endgroup$
1
$\begingroup$

What don't you do the substitution $x=\sinh(x)$ and use $$\cosh^2(x)=\frac{1+\cosh(2x)}{2}\ \ ?$$

$\endgroup$
1
  • $\begingroup$ Because I spent a lot of time doing it this way just to drop it like that for a minor mistake... Looks like it wasn't even a mistake $\endgroup$
    – Plexus
    Feb 21 '18 at 12:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.